(untitled) - Haag, Stephen (Boston, MA., 2003)
The I-Series leads the student through clear, error-free, and unambiguous steps to accomplish tasks that produce a finished document, work sheet or database table. The approach is not simply results-oriented; teaching how to accomplish a task is not enough for complete understanding and mastery. Prior to introducing steps, the authors discuss why each step is important and what roll all the steps play in the overall plan for creating a document, workbook or database. The I-Series Applications textbooks strongly emphasize that students learn and master applications skills by being actively engaged by doing.
Keywords: Microsoft Word.,Word processing